Analisis Proses Perencanaan dan Penganggaran APBD (Studi Kasus pada Pemerintah Kabupaten Bolaang Mongondow) - Paputungan, Amna; Ilat, Ventje; Morasa, Jenny (Universitas Sam Ratulangi, 2017)
Abstract. Local Government Financial Management is a subsystem of State Government Financia Management. It is also a substantial element in operating local governance effectively, efficiently and economically by fulfilling main pillars of government operation. Those main pillars are transparency, accountability, and participative. These pillars are determined by the Indonesian Government Regulation Number 58 year 2005 and Permendagri Number 13 year 2006. The stages include planning and budgeting process, starting from absorption of people’s aspiration, setting up and the implementation of detailed planning and budgeting as regulated by constitutions. There are obstacles in the planning and budgeting process in Local Government of Bolaang Mongondow. Those obstacles are in Musrenbang stage, Local Government Budgeting Team, process of setting up KUA-PPAS and RKA-SKPD, budget discussion between DPRD members and APBD budgeting staff. This research also discusses their efforts to overcome the obstacles in the process of planning and budgeting of Local Government of BolaangMongondow APBD. This is a qualitative case study research. Data were collected by interviews and observation. Respondents are staff involving in the process of planning and budgeting. They are Government employees and members of DPRD in the Local Government of Bolaang Mongondow. This study undertook more than 2 months for collecting its data. Results indicate that the process planning and budgeting of APBD in the Local Government of Bolaang Mongondow has not fulfilled yet the regulations. Results also show that transparency is not yet conducted sufficiently and people’s aspirations have not been absorbed optimally, either bottom up or top down approach. It is, thus, efforts are needed to overcome such obstacles in the process of planning and budgeting of APBD in the Local Government of BolaangMongondow. Keywords: Local government planning and budgeting, people’s aspiration, Permendagri Number 58 year 2005, Permendagri Number 13 year 2006 Abstrak. Pengelolaan Keuangan Daerah merupakan sub system dari Pengelolaan Keuangan Negara serta merupakan elemen pokok dalam penyelenggaraan Pemerintahan Daerah dalam rangka pengelolaan Keuangan Negara dan Daerah yang efektif, efisien dan ekonomis melalui tata kelola pemerintahan yang memenuhi pilar utama yaitu transparansi, akuntabilitas, dan partisipatif. Yang telah diatur dalam Peraturan Pemerintah Nomor 58 Tahun 2005 dan Permendagri Nomor 13 Tahun 2006. Dimana tahapan proses perencanaan dan penganggaran dimulai dari penyerapan aspirasi masyarakat, waktu penyusunan, sampai pada tata cara pelaksanaan perencanaan dan penganggaran sudah diatur sedetail mungkin dalam peraturan perundang-undangan.Proses perencanaan dan penganggaran di Pemerintah Kabupaten Bolaang Mongondow terdapat kendala-kendala dalam hal ini dimulai dari tahapan Musrenbang, peran Tim Anggaran Pemerintah Daerah, proses penyusunan KUA-PPAS, proses penyusunan RKA-SKPD, pembahasan anggaran dengan pihak DPRD dan penetapan anggaran APBD. Sehingga dalam penelitian ini ada upaya untuk mengatasi kendala yang terjadi dalam proses perencanaan dan penganggaran APBD di Pemerintah Kabupaten Bolaang Mongondow. Penelitian ini menggunakan pendekatan kualitatif metode studi kasus, pengumpulan data dilakukan melalui observasi dan wawancara dengan orang-orang yang terkait dalam proses perencanaan dan penganggaran yang berasal dari Aparatur Sipil Negara dan anggota DPRD Pemerintah Kabupaten Bolaang Mongondow. Penelitian ini difokuskan pada Proses Perencanaan dan Penganggaran di Pemerintah Kabupaten Bolaang Mongondow, dengan waktu penelitian kurang lebih 2 bulan. Hasil penelitian menunjukkan bahwa perencanaan dan penganggaran APBD di Pemerintah Kabupaten Bolaang Mongondow belum mematuhi peraturan perundang-undangan yang ada serta belum memaksimalkan transparansi dan keterlibatan masyarakat dalam hal ini pendekatan Bottom Up dan Top Down belum berjalan secara optimal. Sehingga harus ada upaya dalam menghadapi kendala dalam proses perencanaan dan penganggaran APBD di Pemerintah Kabupaten Bolaang Mongondow. Kata Kunci : Perencanaan dan Penganggaran Daerah, Partisipasi Masyarakat, Permendagri Nomor 58 Tahun 2005 Permendagri Nomor13 Tahun 2006